Patterns to Affinities to Labels: Exploring the Roots of “Southern Writing” - Moore, Robert (FOCUS: Papers in English Literary and Cultural Studies, 2006)
Richard Ford, author of the Pulitzer Prize-winning novel Independence Day and a native of Mississippi, has decried the imposing of labels on writers and their work— Southern writer, the Jewish writer, the black writer, the feminist writer. What do such labels do, Ford asks, but load down the particular writer with a burden of presuppositions and stimulate readers to approach the work w ith a fixed set of expectations? (“A Stubborn Sense” 42-43).